A new species of Passiflora L. (Passifloraceae), from Espírito Santo, Brazil - Imig, Daniela Cristina; Cervi, Armando Carlos (Phytotaxa, 2014)
In this paper we describe and illustrate Passiflora junqueirae, a new species for the Brazilian flora. The new species was collected in the Caparaó National Park, Espírito Santo, Brazil, and belongs to the genus Passiflora, subgenus Passiflora, supersection Stipulata, section Granadillastrum.